Influence of Progressive Muscle Relaxation Therapy on Blood Pressure Reduction in Families with Hypertension: A Literature Review - Cahyono, Bagus Dwi; Huda, Nurul; Aristawati, Evy; Kusumadayanti, Hasri Yudha; Susilawati, Endang Fauziah; Salamah, Saidatus (Al-Hijrah Indonesia, 2025)
The risk of disease is related to congenital genetic factors, one of which is hypertension. Hypertension is a condition in which blood pressure increases from normal limits caused by unhealthy lifestyles such as excessive salt consumption, obesity, smoking, consumption of alcoholic beverages, and others. How to reduce high blood pressure is done by administering drugs and non-pharmacological therapy, one of which is progressive muscle relaxation therapy. The method used in this final project report is a literature review by reviewing 1 international article and 6 national articles. The collection process uses the PRISMA method (Prefer Reporting Items for Systematic Reviews and Meta-Analysis), and data analysis uses Thematic Analysis to test articles using compare, contrast, and criticism. Progressive muscle relaxation therapy significantly reduces blood pressure. Blood pressure decreases due to relaxation after administration of progressive muscle relaxation therapy. The authors state that progressive muscle therapy can be used as educational material and can be implemented as a nursing intervention in lowering blood pressure in groups or families with a history of hypertension.